Preoperative sarcopenia and systemic immune-inflammation index can predict response to intravesical Bacillus Calmette-Guerin instillation in patients with non-muscle invasive bladder cancer - Liu, Peng; Chen, Shouzhen; Gao, Xingzhe; Liang, Hao; Sun, Daqian; Shi, Benkang; Zhang, Qiujie; Guo, Hu (Frontiers in Immunology, 2022)
Background: To explore the prognostic significance of sarcopenia and systemic immune-inflammation index (SII) for response to intravesical Bacillus Calmette-Guerin (BCG) in patients with intermediate-, and high-risk non muscle invasive bladder cancer. Methods: We retrospectively analyzed 183 consecutive patients treated in Qilu hospital of Shandong University for a first diagnosis of intermediate and high risk NMIBC. Using computed tomography scans at the third lumbar vertebra level, we calculated skeletal muscle index (SMI). Sarcopenia was defined as SMI <43 cm2/m2 for males with BMI < 25 kg/m2, <53 cm2/m2 for males with BMI ≥ 25 kg/m2, and <41 cm2/m2 for females. The response to intravesical BCG immunotherapy and relapse-free survival (RFS) were analyzed. Results: The area under the ROC curve (AUC) of the BMI, NLR, PLR, and SII for response to intravesical BCG immunotherapy were 0.425, 0.693, 0.631, and 0.702 respectively. Logistic regression analysis demonstrated that sarcopenia and SII were predictors of response to intravesical BCG immunotherapy. The Kaplan-Meier survival analysis showed that the RFS of patients with BCG response, lower SII and no sarcopenia was significantly increased compared with that of patients with BCG non-response, higher SII and sarcopenia, respectively. Subgroup analysis demonstrated that the RFS of patients with high SII and sarcopenia was significantly decreased compared with those with low SII and no sarcopenia in Ta stage subgroup, T1 stage subgroup, non-Cis subgroup, multiple tumor subgroup, single tumor subgroup, tumor diameter≥3cm subgroup and tumor diameter＜3cm subgroup, respectively (P < 0.05). However, there was no significant difference in RFS for patients in CIS subgroup (P > 0.05). Multivariate Cox analysis shown that sarcopenia (p=0.005) and high SII (p = 0.003) were significantly associated with poor RFS. Conclusions: Both sarcopenia and high SII are useful predictors of response to intravesical BCG in intermediate- and high-risk NMIBC patients. Patients with intermediate- and high-risk NMIBC that had sarcopenia or high SII at diagnosis were associated with poor RFS, and the combination of sarcopenia and SII may be a better predictor of RFS.